Exploring the Implementation of Socially Responsible Human Resource Management (SR-HRM) in Enhancing Employee Work Engagement at PT MRP (A Qualitative Study on the Mediating Roles of Perceived Organizational Support and Affective Commitment) - Fatwah, Muhammad Imam; Rakhman, Sitti (Jurnal Multidisiplin Sahombu, 2025)
This study aims to explore and analyze the impact of Socially Responsible Human Resource Management (SR-HRM) on employee work engagement at PT MRP, an insurance company in Indonesia, by examining the mediating roles of Perceived Organizational Support (POS) and Affective Commitment (AC). Using a qualitative approach through in-depth interviews and participatory observations, the findings reveal that SR-HRM practices, such as fairness, inclusivity, continuous training, transparent performance evaluation, and work-life balance support, significantly enhance employee engagement. POS and AC serve as key mediators in strengthening this relationship. Employees who feel supported and emotionally attached to the organization tend to be more motivated and committed. The study underscores the importance of effective internal communication and the integration of SR-HRM into long-term strategic policies to foster a healthy and productive work environment. The results offer practical implications for insurance companies to develop socially responsible HR policies that enhance employee well-being and engagement, ultimately boosting competitiveness. Future research is recommended to expand the scope across various insurance firms and examine additional influencing factors.